PENINGKATAN MOTIVASI BELAJAR DENGAN MENERAPKAN STARTER EXPERIMENTS APPROACH PADA MATERI HUKUM NEWTON SISWA KELAS VIII SMP NEGERI 1 ATAP TAMBANG - Wulan Suryani; Mitri Irianti; Syahril Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The study is aims to improve student’s motivation at VIII grace SMP Negeri 1 Atap Tambang by applying Starter Experiment Apporoach on Newton’s Law. The form of the research is pre- experiments with One Group Pretest- Posttest Design. The subject of the research were the student’s of grace VIII SMP Negeri 1 Atap Tambang 2017/2018 which around 33 students, consis of 18 female and 15 male student’s. The instrument used to collect the data is the ARCS motivation questionnaire and the research data is analyzed by descriptive analysis technique using n-gain. Student motivation IPA Physics increased with application of Starter Experiment Apporoach, improvement of student learning motivation seen on each indicator with indicator of satisfaction followed by indicator of attention and also indicator of confidence and relevance. Thus the application of Starter Experiment Apporoach on Newton's Law can improve students' learning motivation.Keywords: Learning Motivation, Apporoach Starter Experiment